Motivasi Kader Posyandu Desa Krakitan Dalam Meningkatkan Keberhasilan Posyandu Di Masa Pandemi - Anna Uswatun Qoyyimah; Wiwin Rohmawati; Piscolia Dynamurti Wintoro (Stikes Muhammadiyah Klaten, 2022)
The motivation of a cadre is very important because it will affect the willingness of cadres to work hard in completing their work and achieving high work productivity. Cadre motivation is a driving force that makes cadres develop creativity and mobilize all their abilities to optimize posyandu services. This study aims to determine the motivation of cadres in increasing the success of posyandu activities during the pandemic. This research method is descriptive quantitative. The sample in this study was 30 cadres of Krakitan Bayat Klaten Village. The sampling technique uses total sampling. The instrument used is a questionnaire. Data analysis using univariate test. The results showed that most of the cadres in this study had good motivation as many as 22 respondents (73.3%) out of a total of 30 respondents. The conclusion of this study is that most of the Posyandu cadres in Krakitan Village in increasing the success of activities during the pandemic have good motivation.